Pengaruh Konsumsi Ubi Jalar Ungu terhadap Gambaran Histologis Hepar Mencit Setelah Pemberian Beban Aktivitas Fisik Maksimal - Ni Wayan Eka Rahayu Dewi; I Made Jawi; Gaga Irawan Nugraha; Dany Hilmanto (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2018)
Introduction : Purple sweet potato is variant of sweet potatoes and it haveantocyanin pigment that working as antioxidant. This study aims to observe the protective effect of purple sweet potatoes against free radical damage that occurs after strenuous physical activity. Method : This experimental study was conducted on 24 male mice type Balp/C divided into 4 group with randomized control group post-test only design. Histologic examination of the liver cells was done to see the picture of cell necrosis. Statistical analysis used in this study is anova, to know the difference in the number of cells undergoing necrosis in each group. Result : The result of this study shows that the average number of cells undergoing necrosis in high physical activity group (0,667) is bigger than control group (0,00). The average number of cells undergoing necrosis in maximum physical activity group, given purple sweet potato extract (0,167) is lower than group without purple sweet potato extract (0,667), p less than 0.05. Conclusion : Purple sweet potato could reduce the necrosis in liver cell caused by free radical after maximum physical activity